2014
DOI: 10.1016/j.bbrc.2014.10.072
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of hypothalamic murine and human melanocortin 3 receptor transcript structure

Abstract: The melanocortin 3 receptor (MC3R) is involved in regulation of energy homeostasis. However, its transcript structure is not well understood. We therefore studied initiation and termination sites for hypothalamic murine Mc3r and human MC3R transcripts. Rapid Amplification of cDNA Ends (RACE) was performed for the 5’ and 3’ ends of murine and human hypothalamic RNA. 5’ RACE experiments using hypothalamic murine RNA indicated mouse hypothalamus expresses two major Mc3r transcription start sites: one with a 5’ UT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Studies have evaluated the transcript structure of murine Mc3r and human MC3R by examining its untranslated regions (UTRs) [13, 14], which can play important roles in gene expression, mRNA stability, and translational efficiency. Research from our group [14] demonstrated that the murine Mc3r 5′ UTR has two transcription start sites: one 368 bases upstream of the translation start site and another 440 bases upstream, with putative initiator sequences associated with each start site.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies have evaluated the transcript structure of murine Mc3r and human MC3R by examining its untranslated regions (UTRs) [13, 14], which can play important roles in gene expression, mRNA stability, and translational efficiency. Research from our group [14] demonstrated that the murine Mc3r 5′ UTR has two transcription start sites: one 368 bases upstream of the translation start site and another 440 bases upstream, with putative initiator sequences associated with each start site.…”
Section: Introductionmentioning
confidence: 99%
“…Research from our group [14] demonstrated that the murine Mc3r 5′ UTR has two transcription start sites: one 368 bases upstream of the translation start site and another 440 bases upstream, with putative initiator sequences associated with each start site. The murine Mc3r 3′ UTR terminates 1286 bases after the translational stop codon, but with a 787 base splice between consensus splice donor and acceptor sites from 171 bases to 958 bases downstream of the stop codon.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Summary of some bioinformatics tools utilized for the predicting the biological applications of nucleic acids and proteins[42][43][44]50,51,54,[68][69][70][71][72][73][74].Genomic Databases (GenBank, EMBL, DDBJ, Unigene)Genetic testing for identifying chromosomes, genes or proteins Search for nucleic acid/ protein sequences using BLAST…”
mentioning
confidence: 99%